2022
DOI: 10.1021/acsapm.2c01623
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Cellulose Nanocrystals for Aqueous Processing of Thermoplastics

Abstract: Conventional composite formulation of cellulose nanocrystals (CNCs) with thermoplastics involves melt compounding or in situ polymerisation. In this rather unconventional approach, polypropylene (PP) microparticles were finely suspended and stabilized, at varying weight loadings, in aqueous suspensions of amphiphilic CNCs to enable adsorption of the nanoparticles onto the thermoplastic. In order to achieve these suspensions, CNCs were modified with either octyl or hexadecyl groups. These modifications imparted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…1,57,58 Onyianta et al also reported that the chemically modified amphiphilic CNCs can be compounded with polypropylene microparticles in an aqueous system. 59 Figure 5 shows the differences in W ad values between the ACC-BCNFs and various resins in water (the surface free energy parameters of the resins used for the calculations are listed in Table S6). These differences indicate that the acid− base interaction is the predominant component in adhesion interactions in water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,57,58 Onyianta et al also reported that the chemically modified amphiphilic CNCs can be compounded with polypropylene microparticles in an aqueous system. 59 Figure 5 shows the differences in W ad values between the ACC-BCNFs and various resins in water (the surface free energy parameters of the resins used for the calculations are listed in Table S6). These differences indicate that the acid− base interaction is the predominant component in adhesion interactions in water.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…To date, CNFs, which have high mechanical strength, have mainly been used as fillers for nanocomposites. Kondo et al recently proposed an ecofriendly compounding process (i.e., gentle shaking) that involved the underwater adsorption of CNFs onto hydrophobic resin microparticles. ,, Onyianta et al also reported that the chemically modified amphiphilic CNCs can be compounded with polypropylene microparticles in an aqueous system …”
Section: Resultsmentioning
confidence: 99%